Where Is That Crater? Best Practices for Obtaining Accurate Coordinates from LROC NAC Data - Robert V. Wagner; Megan R. Henriksen; Madeleine R. Manheim; Heather M. Meyer; Maria E. Banks; Erick Malaret; Erwan Mazarico; Emerson J. Speyerer; Mark S. Robinson (The Planetary Science Journal)
The Lunar Reconnaissance Orbiter Camera (LROC) Narrow Angle Camera (NAC) images and their derived products make up one of the highest-resolution and most spatially accurate data sets available for the Moon, making them a crucial resource for planners of landed lunar missions. However, it is essential to understand the best uses for each data type and the limits on the accuracy and resolution of the data sets available. With this understanding, users can better interpret and communicate their results. In this paper, we describe what assumptions may be made about the accuracy of LROC NAC images and the various derived products created by the LROC team. NAC digital terrain models and their corresponding orthophotos have the best accuracy of all NAC products, usually better than 10 m horizontally, and should be used where available. Other controlled NAC products usually have accuracies better than 30 m. For areas without controlled products, we describe how to process NAC images to obtain coordinates with the highest possible accuracy. We also recommend best practices for data users interacting with LROC data through online map servers, such as QuickMap or Lunaserv, and for processing LROC data locally using the US Geological Survey Integrated Software for Imagers and Spectrometers.